Ruins - Brooks-Dalton, Lily, 1987- (Grand Central Publishing, Hachette Book Group, 2026)
"Professor Ember Agni is a rising star in archeology, trying to balance an unfulfilling career in academia and a crumbling marriage, all while pursuing her true passion: unearthing a lost empire that no one else believes existed. Just as she's about to give up on the ambitious expedition she spent a decade trying to fund, a message arrives from overseas. A former student claims to have found something extraordinary--an artifact that hints at the forgotten world lying beneath history's tidy surface. With vindication finally within reach, Ember risks everything for the sake of discovery and undertakes an odyssey that will either make her name or ruin her. Driven by unwavering faith in her vision of the past, she challenges the limits of her nation, her colleagues, and herself in order to exhume the missing pieces of how humanity began. But as she journeys deep into an untouched wilderness, in dogged pursuit of a dead civilization, she collides with the wreckage of her own life. On the brink of either discovery or destruction, Ember must choose who she wants to be, and to what kind of world she wants to belong"--